The effects of employee engagement, work environment and organizational learning on organizational commitment in Pejabat Setiausaha Kerajaan Negeri Sembilan / Nor Eliza Azrin Ahmad - Nor Eliza Azrin Ahmad (Faculty of Business and Management, 2017)
This research explores the effects of employee engagement, work environment and organizational learning on organizational commitment in Pejabat Setiausaha Kerajaan Negeri Sembilan. This research also determined the level of organizational commitment at Pejabat Setiausaha Kerajaan Negeri Sembilan, as well as to examine the elements of employee engagement, work environment and organizational learning has significant relationship with organizational commitment and also want to signify which element is the most influence towards organizational commitment and lastly to make a recommendations to improve it. A survey has been conducted among employees who work in Pejabat Setiausaha Kerajaan Negeri Sembilan and total of 140 usable forms of questionnaires were made to deliver among the employees who work in the organization. Based on the finding, research found that the mean of organizational commitment is moderate as show in the finding. Besides that, majority of the respondents agreed that there is a significant positive relationship between employee engagement, work environment and organizational learning towards organizational commitment. On the other hand, employee engagement is the only variable that is influence towards organizational commitment and also there are recommendations that are suggested by researcher to improve the employee engagement in Pejabat Setiausaha Kerajaan Negeri Sembilan.